Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages 10 and shall do so standing only one at the time; they shall address the chairman, and the members shall be seated; the chairman shall call for order as soon as he finds that any member wishes to address the meeting. No member shall be allowed to speak on any one subject more than ten minutes ; any member wishing to reply be allowed the same time. Any member refusing to comply when called to order by the president, or interrupting a member while speaking, shall for the first offence be fined one penny, and two pence for every offence after ; as soon as the discussion is ended, the president shall take the determination by show of hands. The president neglecting to call order, or not levying the fines specified in these rules, shall be fined twopence for each neglect. Should any member of this society come into the club room intoxicated, curse, swear, lay wagers, make use of provoking language to another member, or to the landlord of the house where the society is held, shall for the first offence be fined twopence, and threepence for every offence after, to be paid with his quarter's arrears, or be excluded. 16. That the landlord or landlady of the house where the society is held for the time being be the treasurer, who shall find one or more responsible persons to become security for the moneys entrusted to their care, if required by the society, so long as the members may think proper to hold the society at his or her house. That all cash in hand exceeding £25 shall be drawn from the treasurer by a trustee, and placed in the bank by order of the secretary. 17. That in the event of the death of a member, a certificate from the District Registrar of Deaths must be sent to the secretary. If the deceased has been a member for one year, his wife, heir, or nominee, shall receive the sum of £10; for the death of a free member's wife the sum of £5 will be allowed. No member to be allowed funeral money for more than two wives: no funeral money allowed for the second wife until the first has been dead three years. N.B — The secretary shall not pay the funeral money for a free member or his wife until the certificate of marriage is produced. 345/7/2/2